2018
DOI: 10.1017/s175173111700252x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal methyl donor on the pork characteristics of offspring pigs with prenatal exposure to bisphenol A

Abstract: To explore the effects of maternal nutrition on offspring muscle characteristics, a total of 56 sows were assigned to one of the four dietary groups during gestation: control (CON), or control diets supplemented with methyl donor (MET), bisphenol A (BPA), and combined BPA and MET (BPA+MET). Compared with CON offspring, MET offspring showed a higher meat redness value, but lower glycogen content in the longissimus thoracis (LT). Moreover, compared with CON offspring, MET offspring showed lower LT glycogen synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
3
6
0
1
Order By: Relevance
“…These results indicated that maternal Met supplementation contributed to increased meat production. This effect on improved growth performance was also found in pigs ( Zhuo et al., 2018 ). Methionine is crucial to amino acid metabolism and muscle growth ( Hickling et al., 1990 ), and the coated Met is better absorbed ( Lu et al., 2014 ); therefore, the BW and muscle yield may be more sensitive to coated Met.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results indicated that maternal Met supplementation contributed to increased meat production. This effect on improved growth performance was also found in pigs ( Zhuo et al., 2018 ). Methionine is crucial to amino acid metabolism and muscle growth ( Hickling et al., 1990 ), and the coated Met is better absorbed ( Lu et al., 2014 ); therefore, the BW and muscle yield may be more sensitive to coated Met.…”
Section: Discussionsupporting
confidence: 63%
“…However, it remains unclear whether the effects of dietary Met supplementation could be transmitted to the next generation. In pigs, maternal dietary Met supplementation was proven to affect growth performance and meat quality in offsprings ( Zhuo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the effect of maternal MET exposure during gestation on the growth performance of pig offspring has been controversial. However, maternal nutrition during pregnancy has been found to affect offspring development and has a profound effect throughout the life of the offspring via epigenetic modifications (28,29). Thus, we speculate that the main reason for the different results is the different types and doses of MET.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, we found that dietary MET supplementation during gestation and lactation reduced muscle GP, glycogen and glucose and glucose‐6‐P contents of finishing pigs. The results of our previous studies suggested the reduced levels of CGI‐methylation at the GS promoter persisted throughout the life of the offspring with MET during gestation and persistently silence the muscle GS gene, which is the rate‐limiting factor of glycogen deposition, thereby leading to altered glycogen deposition in later life . Meanwhile, significant differences in ultimate pH 24h values were found in the LD muscle of the MET treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…Betaine, choline, folate, methionine, etc., have been used conventionally as MET due to their biological roles of DNA methylation, improved antioxidative activities, decreased lipogenic enzymes activities and increased hormone‐sensitive lipase activity in adipose tissue . Our previous data showed that gestational diets supplemented with MET lowered plasma homocysteine (Hcy) concentrations of sows improved the antioxidant capacity of sows and newborn piglets, and affected DNA methylation of the muscle glycogen synthase and lactate dehydrogenase genes of newborn piglets and finishing pigs . Some studies have reported favorable effects of maternal MET dietary supplementation on reproduction performance, whereas others found no benefits .…”
Section: Introductionmentioning
confidence: 99%